7, 8-Dichlorobenzo[ghi]perylenetriimide: A versatile synthon for bay-substituted π-extended perylene dyes. (August 2019) - Li, Lei; Zhu, Jun-Yang; Hong, Yu-Jian; Li, Meng-Hua; Xiao, Wang-Chuan; Lin, Mei-Jin
Abstract: Bay-substituted perylene diimide (PDI) dyes are a subject of great interest in both industrial and academic domains in the past decades. As important laterally extended derivatives of PDI dyes, benzo[ ghi ]perylenetriimides (BPTIs) have attracted much attention as non-fullerene acceptors, but their scope for applications has been limited by the lack of substitutions at the remaining two bay positions. Herein, we reported a facile synthesis of a novel, highly valuable synthon, 7, 8-dichlorobenzo[ghi]perylenetriimide (2 ), with two easy leaving chlorine groups at the remaining bay area, which can be further substituted by other functionalized groups through various synthetic strategies. Due to foreseeable applications of core-functionalized BPTIs, this unique synthon is anticipated to open up a fresh ground for optoelectronic materials. Graphical abstract: An unsymmetric and distorted 7, 8-dichlorobenzo[ ghi ]perylenetriimide has been developed, which is demonstrated to be a highly valuable synthon for new bay-substituted π-extended perylene dyes with tuneable optical and redox properties. Image 1 Highlights: A versatile synthon 7, 8-Dichlorobenzo[ ghi ]perylenetriimide has been synthesized for the first time. Two chlorine groups in 7, 8-dichlorobenzo[ ghi ]perylenetriimide can be substituted by various synthetic strategies. The proof-of-the-concept core-functionalized dyes with tuneable optical and redox properties have been demonstrated. This research is of considerable realistic significance for design of other novel π-extended perylene dyes.